Physicians’ Perceived Burden on No-Fault Compensation - 이진우; 김경호; 이상욱; 김대현 (계명의대학술지, 44(1), 2025)
The implementation of a patient-centered no-fault compensation (NFC) system can help protect both patients and healthcare providers, fostering a more supportive and effective clinical environment. This study assessed the perceived burden of NFC on physicians. This study included 199 physicians (male:female, 150 [75%]:49 [25%]; mean age, 45.8 [± 8.42]) from a city in South Korea. Participants completed a structured questionnaire on the perceived burden caused by NFC. Of the physicians, 72.4% conveyed that compensation judgments in no-fault medical accidents were unjust, and 44.7% reported that defensive practices increased healthcare costs by over 40%. A total of 26.9% responded that excessive explanations influenced more than half of their clinical encounters because of concerns about potential legal consequences. Furthermore, 46.7% reported that residents’ training was disturbed by the fear of NFC, while 77.2% responded that student clerkship was disturbed. Most respondents indicated the need to implement a NFC (90.7%), and an autonomous licensing body (83.9%). The high perceived burden of NFC highlights the urgent need for institutional and legal reforms. A structured NFC system must be implemented to distinguish between unavoidable outcomes and genuine malpractice. Proper compensation is critical for sustaining the healthcare system, ensuring quality of care, and enabling ethical patient-centered practices. KCI Citation Count: 0